Intravenous immunoglobulin: a biological corticosteroid-sparing agent in some autoimmune conditions. (September 2017) - Watad, A; Amital, H; Shoenfeld, Y
Intravenous immunoglobulin (IVIg) is increasingly used for the treatment of autoimmune and systemic inflammatory diseases. This compound is effective in a wide range of clinical conditions other than primary immunodeficiency, including autoimmune diseases, inflammatory disorders, infections, organ transplantation, and possibly supportive therapy for cancer. Systemic corticosteroids remain the gold standard treatment for many autoimmune diseases, but their long-term use is associated with complications in diverse organs and systems. Osteoporosis, osteonecrosis, cardiovascular disease, infections, and cancer have been associated with this treatment. Therefore, physicians are occasionally forced to withdraw the treatment with steroids. Biological agents may represent a good alternative, but in addition to being very expensive, these agents may have serious side effects. This review aimed to cover the major advances in the use of IVIg as a steroid-sparing agent in some relevant autoimmune diseases.